Impact of breach of psychological contract on workplace deviant behaviour moderating role of procedural justice among employees of Pakistan - Malik, Sehrish (Management Academic Reserach Society, 2019)
Psychological contract breach may provoke negative attitudes among employees that cause further harmful behaviors. With the help of Social Exchange Theory (SET) the study was conducted to explore the moderating effect of procedural justice between the relationship of psychological contract breach and workplace deviant behaviour. The study was quantitative and cross-sectional survey designed to collect data. Data for the research gathered using a structured questionnaire. The stratified sampling method used to select the sample and final sample comprised of 306 employees working in public sector banks of Gujrat district, Pakistan. Descriptive, correlation, reliability and hierarchal regressions used for testing the hypothesized model for this study. Data were analysed by using IBM SPSS (20.0). A positive relationship found between psychological contract breach and workplace deviant behaviour. Moreover, results showed that procedural justice significantly moderated the relationship of psychological contract breach and workplace deviant behavior. Study limitations and future research directions are discussed.